Enzymatic extract containing lignin peroxidase immobilized on carbon nanotubes: Potential biocatalyst in dye decolourization - Oliveira, Sabrina Feliciano; Luz, José Maria Rodrigues da; Kasuya, Maria Catarina Megumi; Ladeira, Luiz Orlando; Correa Junior, Ary (Saudi Journal of Biological Sciences, 2016)
The majority of the textile dyes are harmful to the environment and potentially carcinogenic. Among strategies for their exclusion, the treatment of dye contaminated wastewater with fungal extract, containing lignin peroxidase (LiP), may be useful. Two fungi isolates, Pleurotus ostreatus (PLO9) and Ganoderma lucidum (GRM117), produced the enzymatic extract by fermentation in the lignocellulosic residue, Jatropha curcas seed cake. The extracts from PLO9 and GRM117 were immobilized on carbon nanotubes and showed an increase of 18 and 27-fold of LiP specific activity compared to the free enzyme. Also, LiP from both fungi extracts showed higher Vmax and lower Km values. Only the immobilized extracts could be efficiently reused in the dye decolourization, contrary, the carbon nanotubes became saturated and they should be discarded over time. This device may offer a final biocatalyst with higher catalytic efficiency and capability to be reused in the dye decolourization process.
Keywords: Lignocellulosic residue; Solid state fermentation; Immobilization; Fungi